(untitled) (Andamios, Revista de Investigación Social, 2012)
This article discusses the use of central concepts to think the specificity of the politics. Punctually, exploring the relationship between the metaphors of order and rupture with the notion of democracy in the works of Georges Sorel, Joseph Schumpeter and Jacques Rancière. To this respect, we discuss the use of formal schemes structured by binary oppositions to think the specificity of the politics, and states that the relationship between order and rupture becomes paradoxical and contradictory, because the political is in an undecidable area.